Loss-of-function mutation of serine racemase attenuates retinal ganglion cell loss in diabetic mice. (October 2018) - Jiang, Haiyan; Du, Jinlin; Song, Juan; Li, Yanqi; Wu, Mengjuan; Zhou, Jing; Wu, Shengzhou
Abstract: Consistent results suggest the promoting roles of serine racemase (SR)/D-serine in retinal neurodegeneration in diabetic retinopathy (DR). However, the direct evidence connecting SR deficiency with retinal neuroprotection in genetic model of diabetes mellitus has not been reported. In this investigation, we explore the effect of absence of functional SR on the degeneration of retinal ganglion cells (RGCs) with a diabetic murine model, Ins2 Akita mice. We established a murine strain with double mutation, termed Ins2 Akita - Srr, by mating heterozygous Ins2 Akita mice with homozygous Srr ochre269 mice. Ins2 Akita retained less RGC in posterior, middle, and peripheral retinae than the counterpart from non-diabetic sibling mice at the age of five or seven months. Ins2 Akita - Srr mice retained more RGC in middle and peripheral–but not in posterior– retinae than the counterpart from Ins2 Akita sibling mice at the age of five months. By contrast, at the age of seven months, Ins2 Akita - Srr mice contained more RGC in peripheral, middle, and posterior retinae than the counterpart from Ins2 Akita . RGCs were identified with retrograde labeling in vivo or with immunolabeling against a RGC-specific transcription factor, Brn3a, in retinal flat mounts. Correspondingly, the aqueous humor of Ins2 Akita - Srr contained less amount of D-serine than sibling Ins2 Akita mice. Thus, SR deficiency significantly prevented RGC loss in diabetic mice. We conclude that D-serine is a critical factor in the degeneration of RGC in DR. Targeting SR expression or activity may be a strategy for ameliorating RGC loss in DR. Highlights: Ins2 Akita or Ins2 Akita - Srr mice developed hyperglycemia and loss of body weight. Loss-of-function mutation of SR significantly prevented RGC loss in Ins2 Akita mice. Loss-of-function mutation of SR significantly reduced D-serine content in the aqueous humor of Ins2 Akita mice.